Stress testing of financial institutions and its improvement - Wang Jian (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is taking Chinese financial institutions as an example, this article explores the application and improvement of stress testing in financial institutions. The subject of research is the research topic is to provide the current situation and improvement suggestions for financial institutions in stress testing. The purpose of the qualifying master’s thesis is to optimize the methods and practical suggestions for stress testing of financial institutions, improve their stress testing level and fit. Based on the results of the research, the author formulated theoretical and practical provisions and proposed parameter optimization and suggestions for financial institution stress testing. The obtained results can further explore the stress testing process of financial institutions and guide them to optimize the current situation to improve the overall testing level.
Стрес-тестування фінансових установ та його удосконалення
Scientific Adviser: Oriekhova Kateryna, PhD in economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; parameter optimization; parameter optimization; parameter optimization; parameter optimization